Application on Reinforcement Learning for Diagnosis Based on Medical Image - Netto, Stelmo Magalhaes Barros; Leite, Vanessa Rodrigues Coelho; Silva, Aristofanes Correa; Paiva, Anselmo Cardoso de; Neto, Areolino de Almeida (IntechOpen, 2008)
None